High mortality in late octogenarians undergoing isolated aortic valve replacement for aortic valve stenosis: EuroSCORE underestimates mortality in this cohort - Kamiya, Hiroyuki; Akhyari, Payam; Pedraza Concha, Anabel Rocio; Tanzeem, Nadine; Kallenbach, Klaus; Lichtenberg, Artur; Karck, Matthias (The thoracic and cardiovascular surgeon, 2012)
Objectives Considering the expanding technology of catheter-based aortic valve implantation, high-risk patients who would not be suitable for conventional aortic valve replacement (AVR) should be identified. Methods From 1997 to April 2007, 190 patients aged from 80 and 89 years old received isolated AVR. Patients between 80 and 84 years old were categorized as the early octogenarians (n = 148) and patients between 85 and 89 years old were categorized as the late octogenarians (n = 42). Results Thirty days mortality in the early and late octogenarians were 6 and 21%, respectively (p = 0.003). The additive and logistic EuroSCORE were 8.0 ± 2.4 and 8.8 ± 1.8 in the early octogenarians and 13.2 ± 11.8 and 14.6 ± 8.7 in the late octogenarians. Multivariate analysis revealed the late octogenarians (OR 6.7, 95%CL 1.8-24.4, p = 0.004) and poor left ventricular function (OR 8.0, 95%CL 1.2-53.5, p = 0.032) as significant risk factors for 30 days mortality. Early octogenarians showed 1-year, 3-year, 5-year, and 8-year survival of 82.4, 67.6, 54.7, and 33%, respectively. Late octogenarians showed 1-year, 3-year, 5-year, and 8-year survivals of 69.0, 66.2, 41.6, 22.3%, respectively. Conclusions Mortality after AVR in the late octogenarians was very high, and was underestimated by EuroSCORE in this patients group. In late octogenarians, catheter-based aortic valve implantation despite relative low EuroSCORE level could be considered as a reasonable alternative.
Gesehen am 12.04.2018